2020
DOI: 10.3390/polym12081815
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Opportunity of Using Plastics from Waste Collected in a Yellow Bag

Abstract: The article presents the results of research aimed at analysing the share of fractions suitable for recycling and pollutants in waste collected in a yellow bag. The research was carried out in an area inhabited by 200,000 people. The amount of waste collected in the communes in yellow containers in 2016–2019 increased systematically in communes: rural by 75.8, urban–rural by 44.9 and urban by 17.8%. The collection efficiency expressed in the degree of collection was the highest and grew fastest in rural areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…One finding was that the higher the population density and population numbers are, the lower the separate collection rate is. Examples come from Germany and the Netherlands (Feil et al, 2017), Poland (Połomka et al, 2020), but also from analyzing data for the EU-28 (Seyring et al, 2016). In their report for the European Commission, Seyring et al (2015) showed that the average separate collection rate of packaging materials and biowaste is, with few exceptions, much lower for the capitals of the EU-28 than for the regarding countries.…”
Section: Separate Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…One finding was that the higher the population density and population numbers are, the lower the separate collection rate is. Examples come from Germany and the Netherlands (Feil et al, 2017), Poland (Połomka et al, 2020), but also from analyzing data for the EU-28 (Seyring et al, 2016). In their report for the European Commission, Seyring et al (2015) showed that the average separate collection rate of packaging materials and biowaste is, with few exceptions, much lower for the capitals of the EU-28 than for the regarding countries.…”
Section: Separate Collectionmentioning
confidence: 99%
“…over-proportionally. Also,Połomka et al (2020) found for their Polish region under investigation that the share of undesired fractions in separately collected lightweight pack-aging waste increased with extension of the collection service and amounts, while the desired fractions decreased. Furthermore,Wang et al (2020) showed that in Notting-…”
mentioning
confidence: 96%
“…Air pollution [26,46] Soil pollution [46] Water pollution [46] Biodiversity [47] Climate change [47] Land use [21] Resource consumption Energy consumption [48] Avoided chemical production [4] Economy Initial investment cost [20,22] Operation and management cost [16] Gate fee [18] Society Public acceptance [34,44] Job creation [44] Public participation [49] Human health [4] Waste prevention behavior [44,50] Policy Regulation [18] Administrative incentive [18] Public organization [15,43] Technical applicability Maturity [22] Feasibility [20] Capacity [20] Product value [51]…”
Section: Environmentmentioning
confidence: 99%